Design and Simulation of MIMO Antenna for Road Side Unit Used inVehicular Communications - Khaing Wai Pyone; Kyaw, Chaw Myat Nwe; Mai, Su Su Yi Mon (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
The main contribution of this work is to create and develop for compact multiple-input multiple-output (MIMO) antennas based on a circular ring monopole antenna. Based on CRMA, four-element MIMO antenna systems are designed with two layers and simulation for 5.9 GHz vehicular communications. The MIMO antenna systems use orthogonally conﬁgured 2x2 CRMA with dual-fed printed on one side of the substrate to achieve good isolation. Design simulation is carried out with the aid of Attar FEKO (2017) Solver. Based on experimental results, the two MIMO antenna systems have an impedance bandwidth of exactly reach between 5.85 to 5.925 GHz, good isolation of less than 15dB.The proposed antenna can achieve VSWR<2 at operating frequency for double layer antenna, with stable and omni-directional radiation pattern. The gain is good and has a peak value of 5.85 dBi. A low envelope correlation coeﬃcient of better than0.02 across the frequency band of (5.85–5.925GHz), which are suitable 2x2 MIMO antenna design for roadside unit vehicular communication.